Optimizing the Role of Bumpekon in Prospering the Community of Pringsewu Lampung - Rohman, Muhammad Nizar; Mukmin, Hasan; Budiwiranto, Bambang; Yanti, Fitri (LPPM Universitas Bumigora, 2023)
The community empowerment is an effort to build community capacity and empower existing human resources through institutional development, facilities, and infrastructure, as well as the development of the three Ps (assistant, counseling, and service). The key to success for the community's welfare in developing villages is the firm touch of initiation, innovation, creation, and collaboration between village officials and the community to realize a shared goal. Village officials need help to carry out village development. Still, it needs support, initiative, and an active role from the community; one of the activities is empowering the community through the Pekon Sriwungu Community Development and Empowerment Program in Improving Welfare in Banyumas District. To realize the empowerment carried out in Pekon Sriwungu, Banyumas sub-district, allocating business capital participation to Pekon-owned Enterprises, taking the background of Pekon Sriwungu, Banyumas District. Based on the conditions on the ground, it can be said that BUMPekon Jaya Makmur Desa Sriwungu, in general, has played a role in improving the welfare of the community wherein carrying out daily activities BUMPekon Jaya Makmur through the management of the Village Tourism business unit has made a significant contribution to Pekon and its people where the presence of Bumpekon has created a center for the community's economic center by providing a particular area for people who have Culinary, Small and Medium Micro Enterprises (MSMEs), souvenirs, homestays and absorb labor from the Pekon community consisting of young people and people who are still productive and open up opportunities investment for people who have venture capital to build new tourist rides.